2021
DOI: 10.1158/0008-5472.can-20-1662
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of G Protein–Coupled Receptor Kinase 2 Promotes Unbiased Downregulation of IGF1 Receptor and Restrains Malignant Cell Growth

Abstract: The ability of a receptor to preferentially activate only a subset of available downstream signal cascades is termed biased signaling. Although comprehensively recognized for the G proteincoupled receptors (GPCR), this process is scarcely explored downstream of receptor tyrosine kinases (RTK), including the cancerrelevant insulin-like growth factor-1 receptor (IGF1R). Successful IGF1R targeting requires receptor downregulation, yet therapymediated removal from the cell surface activates cancer-protective b-arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Subsequently, tyrosine kinases and various types of receptors are investigated as downstream targets of GRK2. Furthermore, it is also engaged in regulation of protein kinases, transcription factors and their regulatory proteins (Smad2/3, IκBα) ( 38 ). Increasing evidence suggests that GRK2, which exhibits the abnormal expression or activity, participates in the regulation of fibrosis-associated pathways, thus may as an essential role engages in the development of fibrotic diseases ( Figure 2 ).…”
Section: Relationship Between Grk2 and Fibrosis-associated Pathwaysmentioning
confidence: 99%
“…Subsequently, tyrosine kinases and various types of receptors are investigated as downstream targets of GRK2. Furthermore, it is also engaged in regulation of protein kinases, transcription factors and their regulatory proteins (Smad2/3, IκBα) ( 38 ). Increasing evidence suggests that GRK2, which exhibits the abnormal expression or activity, participates in the regulation of fibrosis-associated pathways, thus may as an essential role engages in the development of fibrotic diseases ( Figure 2 ).…”
Section: Relationship Between Grk2 and Fibrosis-associated Pathwaysmentioning
confidence: 99%
“…6h, i ). We then used pharmacological and genetic approaches to inactivate or deplete GRK2 and found that paroxetine (PX), a GRK2 small molecule inhibitor 53 , or siRNA-based GRK2 knockdown rescued SPOP reduction induced by glutamine-deprivation (Fig. 5k, l and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GRK2/β-arrestin 2 pairing occurs at low ligand concentrations, has transient signaling effects maintaining receptor homeostasis, and prevents GRK6/β-arrestin 1 complex formation. GRK6/β-arrestin 1 represents a very powerful activator of IGF-IR-mediated β-arrestin 1 signaling and promotes cell proliferation and survival ( 70-72 , 74 ). This type of signaling is triggered by IGF-IR, not only under conditions of abundant natural ligand availability ( 66 ), but also during oncogenic IGF-IR hyperactivation (eg, by Mdm2).…”
Section: Noncanonical Signaling: Igf-ir Uses Gpcr Componentsmentioning
confidence: 99%
“…This type of signaling is triggered by IGF-IR, not only under conditions of abundant natural ligand availability ( 66 ), but also during oncogenic IGF-IR hyperactivation (eg, by Mdm2). It can occur with noncanonical ligands, such as IGF-IR-targeting therapeutic antibodies and LL-37 ( 59 , 65 , 67 , 70-72 , 74 , 75 ). GRK6/β-arrestin 1 signaling downstream IGF-IR not only activates robust MAPK/AKT survival pathways but also inhibits tumor suppressor p53 signaling; however, this occurs at the cost of substantial IGF-IR internalization and degradation ( Fig.…”
Section: Noncanonical Signaling: Igf-ir Uses Gpcr Componentsmentioning
confidence: 99%